Mapeamento de competências docentes: estudo entre acadêmicos de administração - Ramos, Márcio Sampedro (2011)
The changes coming out from the latest years have repercussion on all instances of living in society, generating new social, political and educational demands. Within this new context, it is extremely relevant to rethink the role of the educator, the academic and administrative procedures, as well as the importance of education for the job market (NASSIF; HANASHIRO, 2001). The present study had as general objective to map the teaching competences of the Business Administration course of UFSM in the perception of students and teachers. The research arose from a theoretical model by Alvarez and Diaz (2004) which mapped the following competences: content masterfulness, logical reasoning in the explanation, relationship, organization, evaluation methods, support to students, use of resources, motivation, professional duties, encouragement to classroom participation and theory-practice interaction. The methodology used was a quantitative research of descriptive characteristic. As to the technical procedures, a case study in the Business Administration course of a public higher education institution (IES) was carried out. By analyzing more than 1130 questionnaires, having a sample of the students (226 respondents) and another of the teachers (27 respondents), it was noticed that the teachers were well evaluated, getting means quite above the intermediary value in the scale (2.50). The results still showed that, within these competences, the most important and influential ones in the teaching performance according to the students perception were, in this order: content masterfulness, logical reasoning in the explanation and support to students. Concerning the teachers sample, the results also pointed out the content masterfulness as the most valued competence, followed by logical reasoning in the explanation and encouragement to classroom participation. Thus, it was demonstrated that there is a sort of alignment in the valuation of competences between teachers and students. Among the areas of knowledge in the course, the area of Human Sciences has stood out by presenting the higher means of the competences, within the 29 variables of the construct. The lower means registered were those of the Marketing area.